As narrativas jornalísticas: memória e melodrama no folhetim contemporâneo - Lanza, Sonia Maria (2008)
This work has the objective to analyze the journalistic contemporary narratives in Folha de S.Paulo newspaper and the interface with the melodrama and the serial publication issued in the newspapers from the end of the XIX century to the beginning of the XX century. The newspaper conveys news, not only in the referential way but similar to the seriated narratives way.The printed media does not work in real time like the television, and that makes difficult for the reader the attendance of the facts. That makes us inquire why, nowadays, the seriated narratives are dominant in the television media and why they became a re-encoded paradigm. Why do these articles remain in the reader s memory? To look for answers to these questions, it is necessary the diachronic study of the journalism and how the serial publication structure migrates for other media, the television mostly. In some journalistic programs, the emphasis relapses on the melodramatic gender and the serial publication. For that, the studies of Marlyse Meyer, Thomasseau, and Huppes are essential. Also Morin, Gruzinski, Laplantine, Amálio Pinheiro, Martín-Barbero and Iuri Lotman, through the semiotics of the culture, substantiate this work. Lotman starts from the concept of what text is the least unity of the culture and it has internal definite organization. The journalism, like text of the culture, has distinctive aspects, but while mixing codes it interbreeds and produces new messages to different readers. The Russian theorist points out three functions of the cultural text that corroborate with this research: the communicative function refers itself to the organization of the laws of the language; the creative function that produces the dynamic of the culture and when the text are translated and transmitted into another representational system, they transform themselves into re-encoded messages; and the third function is related to the culture memory. Other concepts of the semiotics of culture like the culture codes, system that shape the culture, border, will base this work. Halbwachs and Zumthor help to reflect about memory. For the first one, the memory allows to remake and to rebuild experiences tested previously and the individual memory is related to the collective memory. For Zumthor, memory and oblivion produce a dynamic created with new codes. This makes possible the substitution of a text for others and this transformation is associated to the selection and fixation of aspects to be maintained. The journalism dramatizes many facts, rescuing elements of the culture to which seem to be present only in other media, making it become a half-breed code. The transformation of the piece of news in serial publication is predominant in the current press and the journalistic narrative is the paradigm reencoded